Penerapan Media Kahoot pada Pembelajaran Bahasa Indonesia Siswa Kelas VII SMPN 2 Wanggarasi Kabupaten Pohuwato - Udin Prasetia; Herson Kadir; Supriyadi Supriyadi (Ideas Publishing, 2023)
This study aims to (1) describe the application of Kahoot in learning Indonesian, (2) describing student responses based on the reflection rubric on the application of Kahoot in learning Indonesian. The method used is a combination method with a descriptive research type through a qualitative approach. The results of the research show that the application of Kahoot In learning Indonesian, it is carried out through three stages of activity, namely the initial, core and final activities of learning. Student responses based on the reflection rubric on the application of Kahoot in learning Indonesian in the Agree and Strongly Agree categories, said that the appearance was attractive, easy to use, learning became easy to understand, and there was an increase in students’ motivation and interest in learning.